Answer:
-10,-6,4,3,7
Step-by-step explanation:
negatives are backwords the higher it gets the smaller the value
Answer:
13
Step-by-step explanation:
6 - 2(-1) + | -5 |
The absolute value means take the non-negative value
6 - 2(-1) + 5
Multiply
6 +2 + 5
Add
8+5
13
9514 1404 393
Answer:
x = 3.6
Step-by-step explanation:
The angle bisector divides the triangle proportionally.
The base segment to the right of the bisector is 6-x, so we can write the proportion ...
x/6 = (6-x)/4
Multiplying by 12, we get ...
2x = 3(6 -x)
5x = 18 . . . . . add 3x
x = 18/5 . . . . divide by 5
x = 3.6
_____
<em>Alternate solution</em>
Since the base of the triangle is given as a left-part and a sum-of-both-parts, we can write the proportion the same way:
left-part / sum-of-both-parts = x/6 = 6/(6+4)
Then the solution is x = 6(6/10) = 36/10 = 3.6.
Doing it this way avoids having x on both sides of the equation, so makes solving the equation be "one step."
Answer:
Step-by-step explanation:
f(x) = (x + 3)(x + 12)
f(x) = x^2 + 3x + 12x + 36
f(x) = x^2 + 15x + 36
To be parallel with that line the equation has to have the same slope as the equation given, like y = 10x + 3.